Spain : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Spain. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2017)
This 2017 Article IV Consultation highlights continued strong, balanced, and employment-intensive expansion of the Spanish economy during the first half of 2017; the recovery reached a significant milestone when real GDP surpassed its precrisis peak. The economy grew by 3.3 percent in 2016 and is expected to expand by 3.1 percent in 2017. Past structural reforms, wage moderation and resulting cost competitiveness gains, favorable monetary and external conditions, and fiscal relaxation have provided impetus to the recovery. The banking system has become more resilient since the last Financial Stability Assessment Program. As some external tailwinds dissipate, economic activity is projected to moderate to 2.5 percent in 2018 in the absence of any major boost in productivity growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet